A arte de Dostoiévski: a polifonia e sua relação com a palavra da diferença - Tagliacozzi, Gabriel Viviani (2024)
Based on Mikhail Bakhtin's work titled "Problems of Dostoevsky's Poetics," the aim of this writing is to express and articulate the concept of polyphony coined by Bakhtin in relation to the artistic works of the Russian author Fyodor Dostoevsky. In this sense, understanding Dostoevsky's works as innovative artistic creations, Bakhtin contrasts the polyphonic aesthetic construction with Western monologic works. Therefore, to comprehend the concept of polyphony, as well as the innovative expression that pervades Dostoevsky's art, it is important to highlight the characteristics that comprise this concept, in addition to relating it to Dostoevsky's own works that support it. In this regard, with a strong foundation in Bakhtin's concept of polyphony when considering Dostoevsky's artwork, the following points regarding the Russian artist's novels are noticeable. Firstly, it's crucial to emphasize that Dostoevsky's artwork is inconclusive, allowing for a multitude of interpretations, as a variety of affects reach each reader individually, with the author himself distancing as a determining and conclusive figure. In this vein, Dostoevsky moves away from the characteristic monologic tone of Western novels and creates original polyphonic-type novels. Thus, Dostoevsky's polyphonic art destabilizes the monologic model, which seeks to place the final and decisive word of the author within the mouth of a specific hero or throughout the entirety of a single work. In contrast, in Dostoevsky's works, the author's voice spreads through the characters, sometimes prominently, while at other times it may be absent. Furthermore, there are no conclusive passages in Dostoevsky's works; everything is in motion, in a state of becoming and occurrence. In this sense, the reader also becomes active and integral, being another singular individual composing the dialogic structure of Dostoevsky's art. Thus, one of the points I emphasize is the value of the word of difference, of expressing singularity, and also of the mode of thought as something constantly in motion in contact with the words of others. Therefore, the idea here is not to definitively close Dostoevsky's characters around a given moral value, or to determine what moral values Dostoevsky himself possesses as a person. Instead, the path taken is to express how each character holds a unique perspective on life, perspectives permeated by the word of difference but not defined by it in an objectified manner. Additionally, to connect the aforementioned with other thinkers, the concept of minor literature created by Gilles Deleuze and Félix Guattari has been used. The viewpoint of these philosophers aligns with Bakhtin's concept and Dostoevsky's art, as they precisely embody the active sense of difference values. To conclude this writing, I have presented how Dostoevsky himself expressed his viewpoint regarding the function of art in society.